Inclusive Education and the Causes of School Dropout: The Case of the Kadey Division of Batouri; East Region of Cameroon (International Journal of Scientific Research and Management (IJSRM), 2020)
The United Nations’ Sustainable Development Agenda for inclusive education has pushed governments in several countries to sign international treaties and conventions to adopt policies and promote equal access to education by every child as a basic human right. Providing all people with education represents a fundamental part of the essential and ultimate aim of enhancing individual happiness and well-being. Nonetheless, for some reasons the objectives for inclusive education have been inhibited by variety of factors resulting to high rate of illiteracy and unprecedented school drop outs most especially in developing countries. It is on this premise that this study is aimed at exploring factors influencing school dropout in the Kadey Division of Batouri; East region of Cameroon. The study is supported by the philosophical underpins of subjectivism ontology and interpretivism epistemology and data was sourced using in-depth interview involving four (4) focus groups consisting of twenty (20) education stakeholders in the Kadey division of Batouri. The analysis was concluded using grounded theory approach and the principle of theoretical saturation was observed to justify the appropriateness of the sample size. The study revealed that school dropout in the Kadey division is influenced principally by economic factors consisting of employment opportunities and financial constraint. The availability of mining activities create opportunities for unskilled jobs for pupils and students whereas, extreme poverty prevents parents to cover school expenses. Other factors such as inadequate infrastructure social, cultural, political and pedagogy constrains were equally identified. This study recommends that academic stakeholders through the Parent-Teachers Association should work closely with the parents to encourage their children of the necessities of quality and sustainable education. It is essential for parents to be aware of the importance of education and to take appropriate measures to keep sending their children to school and fulfil their goals. The government on their part should provide assistance such as infrastructure and teachers to support school administrators achieve academic objectives in the Kadey Division of Batouri East Cameroon